Unusual presentation of a tooth associated with an adenomatoid odontogenic tumour. (2nd June 2019) - Patel, Nimit J; Toms, Simon; McDonald, Fraser; Johnson, Joanna; McArdle, Louis
Abstract : Unilocular radiolucent lesions of the dental hard tissues can present regularly, however they are impossible to diagnose definitively without appropriate imaging and histopathology. A case is reported that involves a 14-year-old that presented with a history of an unerupted maxillary first premolar. An initial Dental Panoramic Tomograph (DPT) did not identify any localized opacities and was diagnosed as a dentigerous cyst. A Cone Bean Computed Tomogram (CBCT) identified calcified opacities resulting in a re-evaluated radiological interpretation. With the help of a multidisciplinary approach, the removal of the benign lesion allowed orthodontic traction to extrude the tooth and for it to be brought into alignment. CPD/Clinical Relevance: This report highlights the importance of three-dimensional imaging as an adjunct to aid diagnosis and highlights the importance of multidisciplinary teams in the management of clinical challenges.